Rancang Bangun Pembangkitan Generator Marx 10 Tingkat pada Uji Kapasitor 220 pF dan Lightning Protector - Rodiah, Yuli; Putri, Nilda Tri; Anggraini, Ika Novia; Herawati, Afriyastuti; Rizki, M. (UNIB Press, 2022)
The Marx generator circuit is an impulse voltage multiplier that is used to represent lightning overvoltage and switching overvoltage. In this research, a 10-level Marx Generator impulse generator design was carried out by varying the distance between the spark gaps of 2.5mm, 5.0mm, 7.5mm, and 10.0mm and the test load was a 220pF capacitor and a lightning protector. The results of the design and simulation of the 10-level Marx Generator produce an impulse voltage according to the IEC 60060-1 lightning impulses standard, which is 20.20kV with a wavefront and tail time of 2.29 µs and 52.3 µs. The test results for the 220pF capacitor load at a distance of 2.5 mm, the resulting voltage is 23.5 kV with a wavefront and tail time of 1.7 µs and 25 µs, while the lightning protector test load produces a voltage of 24 kV, with a wavefront and tail time of 2.1 µs and 43 µs